Traditional Game “Pukang” as a Medium for Social Interaction: A Case Study in Balerejo Village, Lampung - Dena Alinda; Karsiwan; Lisa Retno Sari (CV. Yazri Aksara Nusantara, 2025)
Purpose –This study explores the role of Pukang, a traditional spinning game from Lampung, as a medium for social interaction and cultural preservation within the multicultural community of Balerejo Village, East Lampung. It addresses the declining presence of traditional games due to digital entertainment and emphasizes their continued social and educational relevance. Design/methods/approach – Using a qualitative case study approach, data were gathered through in-depth interviews with three key informants, direct observation of social interactions during Pukang play, and supporting documentation. The data were analyzed using Miles and Huberman’s interactive model to interpret the social meaning embedded in the game. Findings – The findings reveal that Pukang serves as a platform for intergenerational and cross-status social interaction, fosters healthy competition while nurturing social solidarity, and functions as an instrument for preserving local cultural heritage imbued with educational and social character values. Despite challenges posed by modernization and digital entertainment, Pukang remains relevant as an effective medium for social bonding and offers significant potential for integration into social education curricula that emphasize local wisdom and community engagement. Research implications/limitations – While offering insight into local wisdom-based education, the study is limited to one village and a small sample. Broader studies are recommended to assess the game's integration into formal education and its appeal to younger digital-native generations.